Breast fine-needle aspiration cytology reporting using international academy of cytology Yokohama system: A single institution experience - Sreevidyalatha GM; Balaji TG; Manjunath L; Shashikala P Krishnamurthy (Asian Journal of Medical Sciences, 2023)
Background: Worldwide breast malignancy is the major cause for mortality among women. Screening and early detection are crucial. Grey zones of uncertainty in cytomorphological differentiation of benign from malignant lesions can be overcome by Yokohama system of classification. Aims and Objectives: The objectives of this study are as follows: (1) To categorize Breast fine needle aspiration cytology (FNAC) samples according to the international academy of cytology (IAC) Yokohama system. (2) To assess the diagnostic accuracy, sensitivity, specificity, and risk of malignancy (ROM) for each category. Materials and Methods: A retrospective study of 144 breast FNAC cases with histopathological diagnosis was done based on Yokohama System from January 2018 to December 2020. ROM in each category was calculated. The study results were analyzed for sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) considering histological diagnosis as the gold standard. Results: Recategorization of 144 cases with histopathological diagnosis was done according to Yokohama system as insufficient material, benign, atypical, suspicious for malignancy, and malignant. The respective ROM for each category was, 7.6% for Category-1 (Insufficient), 15.26% for Category-2 (Benign), 65.38% for Category-3 (Atypical), 83.33% for Category-4 (Suspicious), and 99.18% for Category-5 (Malignant). Considering malignant cases as positive, sensitivity – 86.75%, specificity – 97.32%, PPV – 99.19%, NPV – 66.06%, and accuracy of 88.96% were deduced. Conclusion: Incorporation of IAC Yokohama system to categorize breast cytopathology using uniform terminologies provides diagnostic clarity, consistency, and accuracy in reporting, which in turn helps the clinician to predict the ROM and patient outcome.